2005
DOI: 10.1038/sj.bmt.1704798
|View full text |Cite
|
Sign up to set email alerts
|

ESHAP plus G-CSF as an effective peripheral blood progenitor cell mobilization regimen in pretreated non-Hodgkin's lymphoma: comparison with high-dose cyclophosphamide plus G-CSF

Abstract: Summary:The ESHAP (etoposide, methylprednisolone, high-dose cytarabine, and cisplatin) regimen has been shown to be effective as an active salvage therapy for lymphoma.Mobilizing stem cells following ESHAP should decrease time to transplantation by making separate mobilizing chemotherapy (MC) unnecessary, while controlling a patient's lymphoma. We therefore assessed the mobilization potential of ESHAP plus G-CSF in 26 patients (ESHAP group) with non-Hodgkin's lymphoma (NHL) and compared these results with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Three other studies 19,20,35 have also reported the use of ESHAP as a mobilization regimen in NHL and HD. It is difficult to compare our results with other reports due to the difference in patient population, type and dosing of growth factors, stem cell collection technique and the machine used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other studies 19,20,35 have also reported the use of ESHAP as a mobilization regimen in NHL and HD. It is difficult to compare our results with other reports due to the difference in patient population, type and dosing of growth factors, stem cell collection technique and the machine used.…”
Section: Discussionmentioning
confidence: 99%
“…Both ours and Watts 20 study showed that 470% patients required only one apheresis. Lee et al 35 described 26 patients with different types of NHL. All the Data in median days.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy to improve the yield may be to select ESHAP/G-CSF priming for lymphoma patients, for whom this appears to be superior. 27,28 The optimal dose of G-CSF in combination with cyclophosphamide is unknown. In our study, no difference in outcome was found between the different priming regimens, but since only 11% did not receive 5 mg/kg G-CSF and only 17% did not receive 2 g/m 2 cyclophosphamide, this study has limited value in excluding a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Among patients treated and mobilized with non-HDC regimens, 67 received ESHAP (etoposide, methylprednisolone, high-dose cytarabine and cisplatin) with (n ¼ 14) or without Rituximab (n ¼ 53); 13 were treated with a modified CALGB protocol 14 (CY, VCR, high-dose MTX, ifosfamide, VP-16, Ara-C, dexamethasone and doxorubicin); 10 received high dose Ara-C; 5 were treated with DHAP (dexamethasone, high-dose cytarabine and cisplatin); 5 received CODOX-M/IVAC (CY, doxorubicin, high-dose MTX/ifosfamide, etoposide and high-dose cytarabine); 5 were treated with CYVE (high-dose cytarabine with VP-16); and 3 received ESHAOx (etoposide, methylprednisolone, high-dose cytarabine and oxaliplatin). Other non-HDC regimens included HDC plus VP-16, CHOP and ifosfamide with VP-16.…”
Section: Pbpc Mobilization and Harvestmentioning
confidence: 99%